Estimation of Overall Fatigue Life of Jack-up Leg Structure - Dinh Quang Cuong; Vu Dan Chinh (Salehan Institute of Higher Education, 2022)
Jack-up platforms are designed to work in three conditions: Transit, Preloading and Operating. The fatigue life of the jack-up platforms in operating condition will be determined to be similar to that of offshore fixed steel structures. In preloading conditions, fatigue damage is usually ignored. Up to now, the fatigue damage of the jack-up leg structure in transit conditions has been calculated at approximately 20% of the total fatigue damage of the jack-up leg structure in two conditions (transit and operating). The approximate calculation method is usually accepted by consultants and register agencies. If the approximation is used, the fatigue life of the jack-up leg structure will be calculated only as for the jacket structure of the fixed offshore structure, with 80% of the allowable fatigue life based on standards. The approximation proved to have many disadvantages: the different travel times of each jack-up rig cannot be mentioned; hot spots that need to be maintained during the transit condition have not been pointed out; it is difficult to guarantee the safety of the jack-up leg structures in the transit condition. In order to overcome the limitations of the approximation method, this paper will propose a method to predict the overall fatigue life of the jack-up leg structure in three main problems. Firstly, we use the analysis method of fatigue of fixed steel offshore structures for jack-up leg structures in operating conditions. Secondly, we suggest a method to analyze the fatigue of the structures in transit conditions. Herein, motion analysis and determination of inertia forces on the leg structure are performed by the Boundary Element Model (BEM) in SACS software. Then the inertia forces are assigned to a Finite Element Model (FEM) in SACS to decide the internal forces of the structures. Hotspot stresses are determined by combining nominal stress from FE analysis results with a concentrated stress factor from the analysis of joint local models in the ANSYS program. Then, fatigue damage and fatigue life of hotspots of the structure are determined in the transit condition. Finally, a formula is suggested to determine total fatigue damage in operating conditions and transit conditions with different cases in relation to different fraction factors. These results are used to predict fatigue life corresponding to the most dangerous cases of structural joints. These new suggestions are applied to fatigue analysis for jack-up Tam Dao 05. Currently, the Tam Dao 05 platform has been operating in the Vietnam East Sea. Doi: 10.28991/CEJ-2022-08-03-06 Full Text: PDF